2022
DOI: 10.3390/pharmaceutics14020237
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prescription of Strong Opioids for Chronic Non-Cancer Pain in Primary Care in Catalonia: Opicat-Padris-Project

Abstract: In chronic non-cancer pain (CNCP), evidence of the effectiveness of strong opioids (SO) is very limited. Despite this, their use is increasingly common. To examine SO prescriptions, we designed a descriptive, longitudinal, retrospective population-based study, including patients aged ≥15 years prescribed SO for ≥3 months continuously in 2013–2017 for CNCP in primary care in Catalonia. Of the 22,691 patients included, 17,509 (77.2%) were women, 10,585 (46.6%) were aged >80 years, and most had incomes of <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some physicians have tried to reduce opioids and other intravenous injections after witnessing this unintentionally. [ 17 , 18 ]. However, intramuscular, subcutaneous, and other drug injections do not prevent general or local complications [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…Some physicians have tried to reduce opioids and other intravenous injections after witnessing this unintentionally. [ 17 , 18 ]. However, intramuscular, subcutaneous, and other drug injections do not prevent general or local complications [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…Tapentadol has been marketed in Australia, Europe, and the USA for at least 12 years 1▪▪ and it is being increasingly used 2,3. Tapentadol was synthetized using rational drug-design to create a molecule with µ-opioid receptor (MOR) agonism and noradrenalin reuptake inhibition (NRI) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies suggest that women are more likely to be prescribed opioids in CNCP. Perelló-Bratescu et al (2022) analyzed the trends in the prescription of strong opioids for this pathology in primary care in Catalonia, Spain, using a descriptive, longitudinal, retrospective population-based study from 2013 to 2017. This study showed that there was a sustained increase in the prescription of strong opioids at high doses, and in mainly elderly patients, predominantly low-income women.…”
Section: Introductionmentioning
confidence: 99%